Problem aspects of legal regulation of responsibility for the crime of aggression - Lobach, Dmitry V. (Journal of the Belarusian State University. Law, 2021)
The article examines the key problems associated with the legal regulation of liability in modern international law. The author of the article analyses seven key problems, which in their totality reduce the law enforcement potential of the norms regulating responsibility for committing the crime of aggression. In particular, such problems include the lack of a unified definition of state as part of the crime of aggression; a plurality of approaches to the definition of state sovereignty as an object of criminal encroachment; the complexity of the lawful use of armed force in the context of the state’s realisation of its right to self-defense; the problem of the lawful use of armed force in the context of humanitarian intervention; the absence in the practice of international relations and in international law itself of universal criteria to determine the sufficiency of a violation of international peace to qualify an act as a crime of aggression; the problem of an expanded understanding of armed force as an act of aggression; the contiguous nature of some forms of aggression with lawful actions related to ensuring national security.
Keywords: international crime; crime of aggression; international criminal responsibility; self-defense; cyber security; cyber threats